Management of life skills-based education in a girls' pesantren during the COVID-19 Pandemic: A case study in Yogyakarta - Nasrulloh, Rifqi Syarif; Sutiyono, Sutiyono (Harmoni Sosial: Jurnal Pendidikan IPS, 2024)
Pesantren, as an integral part of Indonesia's educational and cultural heritage, faced unprecedented challenges during the COVID-19 pandemic. These challenges included adapting their management and teaching methods to sustain their dual objectives: spiritual development and life skills-based education. This study examines the educational management strategies implemented by a girls' pesantren in Sleman, Yogyakarta, focusing on life skills education. Using a qualitative research design, data were collected through purposive sampling, participatory observation, and structured interviews with key stakeholders, including the pesantren's founder and educators. The study employs the ADDIE framework"”planning, organizing, implementation, and control"”to evaluate life skills-based educational management. The findings reveal that while the planning and organizing stages align with the institution's strategic goals, the implementation and supervision require improvement in terms of documentation and task formalization. Nevertheless, the application of practical learning and direct mentoring has effectively enhanced the students' independence and vocational competencies. This study contributes by providing a replicable life skills-based educational management model for similar pesantren and serves as a reference for policymakers in improving the quality of pesantren education in the future.